Media Capacity Building in Sudan: A Measure of Success?. Issue 2 (3rd April 2018) - Baker, Nigel; Scott, Helen
ABSTRACT: A five-year, media capacity-building programme in Sudan gives some valuable pointers about how to keep a media-development programme alive—and the positive results that can be achieved through perseverance and a collaborative effort by stakeholders. The results included the introduction of a new reporting style that highlighted issues of public interest, not previously understood, and journalists who were given the confidence to minimise self-censorship.